Deuterium retention in tungsten oxide: the role of oxide damage - Mykola Ialovega; Celine Martin; Cédric Pardanaud; Elodie Bernard; Martiane Cabié; Andrea Campos; Christian Grisolia; Marco Minissale; Thomas Neisius; Thierry Angot; Régis Bisson (Nuclear Fusion)
Tungsten (W) is a common plasma-facing material in nuclear fusion devices. It readily oxidizes in the presence of oxygen, forming tungsten oxides, particularly WO _3 , which may modify deuterium retention. This experimental study investigates mechanisms of the evolution of deuterium retention in a thermally stable ${\sim}100$  nm WO _3 layer grown by thermal oxidation of a W substrate at 1073 K under low pure oxygen pressure of 7 Pa. 500 eV D $_2^+$ deuterium implantation and Temperature Programmed Desorption (TPD) were used to explore deuterium trapping and release from the oxide as a function of incident ion fluence and storage time in ultra high vacuum. Upon deuterium irradiation, the formation of a W-rich layer on the surface of the oxide is evidenced with x-ray photoelectron spectroscopy. After successive implantation/TPD cycles corresponding to an accumulated deuterium fluence ${\gt}10^{21}$  D m ^−2 , the appearance of an amorphous oxide encapsulated between two W-rich layers is observed with transmission electron microscopy. Following this high fluence deuterium implantation, deuterium retention increases by a factor of 10. The findings provide insight into the behavior of tungsten oxides under deuterium implantation, emphasizing the importance of considering its thermal stability and its structural modifications at the surface of tungsten plasma facing components.